Love in the Last Days: The Eschatological Marking of Bodies Resembling an Infinitely Queer Desire - Méndez Montoya, Angel F. ca. 21. Jh. (Concilium, 2019)
The complexities of the meaning of 'queering' as a body that is inclusive, dynamic and eschatological (in constant development) spark some theological reflections mentioned here briefly and rather piecemeal.